The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3102/0091732x18821125
|View full text |Cite
|
Sign up to set email alerts
|

Changing How Writing Is Taught

Abstract: If students are to be successful in school, at work, and in their personal lives, they must learn to write. This requires that they receive adequate practice and instruction in writing, as this complex skill does not develop naturally. A basic goal of schooling then is to teach students to use this versatile tool effectively and flexibly. Many schools across the world do not achieve this objective, as an inordinate number of students do not acquire the writing skills needed for success in society today. One re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
192
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(312 citation statements)
references
References 74 publications
9
192
0
16
Order By: Relevance
“…Such instruction appears to have been relatively uncommon, however, based on survey and observational research conducted in the area of writing. In reviewing this literature, I found that most teachers were not adequately prepared to teach writing and that they devoted little time to writing or writing instruction (Graham, 2019). Reading and writing instruction is not effectively integrated when one of the ingredients occurs infrequently.…”
Section: The Futurementioning
confidence: 99%
“…Such instruction appears to have been relatively uncommon, however, based on survey and observational research conducted in the area of writing. In reviewing this literature, I found that most teachers were not adequately prepared to teach writing and that they devoted little time to writing or writing instruction (Graham, 2019). Reading and writing instruction is not effectively integrated when one of the ingredients occurs infrequently.…”
Section: The Futurementioning
confidence: 99%
“…Place is a central concern in an approach informed by a social ecological model which posits that both social and environmental factors that can relate to place can shape student attainment, achievement, and motivation (Saracho and Spodek, 2006). While there is a gap in literacy attainment between urban and rural schools (Gorur and Wu, 2015), little is known of how place and space impact upon reading and writing skills and attitudes beyond material resourcing, size, and staffing differences (Graham, 2019;Lamb et al, 2014). Analysis of Australian National Assessment Program -Literacy and Numeracy (NAPLAN) testing data indicate that "students in low socio-economic areas start behind, and make less progress in school," and that "many regional and rural students make up to two years less progress than students in inner city areas between Year 3 and 9" (Goss and Sonnemann, 2016: 2).…”
Section: Place and Resourcingmentioning
confidence: 99%
“…It conveys a message to a reader for a specific reason. However, it is not an easy skill to acquire (Graham, 2019). It becomes further complicated in case of L2 and FL writers (Al Badi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They have many deficiencies in writing accuracy and fluency (Althobaiti, 2015;Althobaiti, 2019). The students also suffer from a lack of motivation and involvement when writing (Graham, 2019).…”
Section: Introductionmentioning
confidence: 99%